Challenges of developing professional practice in vocational education and training - The Kosovo case - Gjergjaj, Florentina; Gojani, Anton; Gojani, Hajrije Devetaku (Edelweiss Applied Science and Technology, 2025)
Challenges in vocational education and training (VET) remain among the primary issues confronting Kosovo’s education system. The most critical challenges are structural and institutional, particularly those related to implementing professional practice, enhancing youth employability, and aligning VET with labor market demands. The study employed both quantitative and qualitative methods, conducted across five municipalities, nine schools, and forty partner companies. Participants included 125 students, nine school coordinators responsible for professional practice, and thirty-nine company mentors. Findings indicate that the absence of structured institutional cooperation, the predominance of theoretical content, and inadequate practical infrastructure significantly undermine VET quality. They further highlight the crucial role of trained instructors as a decisive factor for process effectiveness. A comparison with successful European models, particularly the German and Swiss systems, underscores gaps in Kosovo’s context, emphasizing the need for institutionalized partnerships, infrastructure modernization, and curriculum reform. The study recommends developing a national strategy for professional practice, training and certifying instructors, and introducing fiscal incentives for businesses offering placements. These conclusions provide a foundation for sustainable policies and strategic interventions aimed at improving youth employability and fostering long-term economic growth.